Research on the effect of uncertain rewards on impulsive purchase intention of blind box products - Zhang, Yi; Zhou, Hang; Qin, Jian (Frontiers in Behavioral Neuroscience, 2022)
Since 2019, China has gradually seen a “blind box” boom, and young people have quickly become the main buying force of blind boxes, promoting the continuous development of the blind box industry. Previous studies have shown that uncertainty in events with positive prospects can play a more positive role than certainty. However, how does uncertainty in the blind box affect consumers’ emotions and cognition and trigger subsequent consumption decisions? To clarify the internal mechanism of this process, this paper takes the blind box as the research object and constructs the mechanism model of perceived uncertainty on consumers’ impulsive purchase intention, based on Stimulus-Organism-Response (SOR) theory. In addition, the curiosity variable and perceived luck variable are introduced according to the information gap theory and optimism theory. On this basis, we conduct an empirical analysis by means of a questionnaire survey. The results show that perceived uncertainty has a positive impact on consumers’ impulsive purchase intentions, in which curiosity plays a mediating role. Besides, perceived luck positively moderates the impact of perceived uncertainty on impulsive purchase intention. This study clarifies the internal impact of perceived uncertainty on impulsive purchase intention of the blind box and enriches the basic theory of uncertainty reward and purchase intention. At the same time, we also offer related recommendations for future enterprises to learn from the marketing model of uncertain rewards.